2015
DOI: 10.1183/09031936.00020714
|View full text |Cite
|
Sign up to set email alerts
|

Airway wall thickness associated with forced expiratory volume in 1 second decline and development of airflow limitation

Abstract: Airway wall thickness and emphysema contribute to airflow limitation.We examined their association with lung function decline and development of airflow limitation in 2021 male smokers with and without airflow limitation. Airway wall thickness and emphysema were quantified on chest computed tomography and expressed as the square root of wall area of a 10-mm lumen perimeter (Pi10) and the 15th percentile method (Perc15), respectively. Baseline and follow-up (median (interquartile range) 3 (2.9-3.1) years) spiro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…Eltboli and colleagues [24] reported that there is a strong correlation between peripheral blood and bronchial eosinophils and reticular basement membrane thickening and suggested that the peripheral blood eosinophil count does identify COPD subjects with a greater tissue eosinophilia. A recent study documented that airway wall thickness is independently associated with a stronger decline in lung function [25]. On the basis of our results, we completely agree with Brightling and George [26] that it is too simplistic to consider the eosinophil as the crucial element leading the development of airflow obstruction, but it might play a role given the right environment and opportunity.…”
Section: Discussionsupporting
confidence: 89%
“…Eltboli and colleagues [24] reported that there is a strong correlation between peripheral blood and bronchial eosinophils and reticular basement membrane thickening and suggested that the peripheral blood eosinophil count does identify COPD subjects with a greater tissue eosinophilia. A recent study documented that airway wall thickness is independently associated with a stronger decline in lung function [25]. On the basis of our results, we completely agree with Brightling and George [26] that it is too simplistic to consider the eosinophil as the crucial element leading the development of airflow obstruction, but it might play a role given the right environment and opportunity.…”
Section: Discussionsupporting
confidence: 89%
“…53 Hoesen et al showed greater associations between pi10 measurements and FEV 1 . 56 In the same study, increased pi10 airway wall thickness was also shown to be associated with FEV 1 decline. 56 Airway wall measures from CT were also shown to independently predict bronchodilator responsiveness in COPD subjects.…”
Section: Ct Measures Of Copdmentioning
confidence: 83%
“…56 In the same study, increased pi10 airway wall thickness was also shown to be associated with FEV 1 decline. 56 Airway wall measures from CT were also shown to independently predict bronchodilator responsiveness in COPD subjects. 57 Recently, Gietema and colleagues showed that the airway wall thickness measurement on CT was significantly associated with decreased quality of life in COPD subjects after adjusting for age, current smoking status, pack-years of smoking, body mass index, and FEV 1 .…”
Section: Ct Measures Of Copdmentioning
confidence: 83%
“…The correlation between wall dimensions and pulmonary function tests (PFT) increase as more peripheral and smaller airways are measured . However, CT scan measurements at this scale are known to overestimate wall thickness (WT) and underestimate lumen size .…”
Section: Introductionmentioning
confidence: 99%